The Romanian Căluş: Symbol of National Identity - Camelia, Firică (University of Tartu, Estonian National Museum, Estonian Literary Museum, 2018)
Of all Romanian dances with ritual functions the most archaic and dynamic is the căluş, a custom of great complexity in its functionality and manifestation, in which dance prevails. Over the course of time, the dance aroused the admiration and interest of many scholars due to the ancient ritual elements it contains, as well as for its spectacular virtuosity and the beauty of the performance and music. The purpose of this study is to reveal the meanings and functions of the căluş, primarily at the social level, in its natural environment – the traditional Romanian village – and to make an analysis of the key moments, the logical order of the dance sequences, gestures and ritual acts, the importance of its props and of group composition and organisation.